Feeding rape affects Tan sheep growth and slaughter performance, meat quality, intramuscular fat deposition, and relative gene expression - Jie Yang; Fan Feng; Hao Li; Qiaoxian Gao; Guosheng Xin (Journal of Applied Animal Research)
This study investigated the impact of feeding rape supplementation on growth performance, slaughter performance, meat quality, and the gene expression of associated traits in Tan sheep. 40 castrated male Tan sheep were divided into four groups of 10 animals each. The control group (Group A) was fed with a basal diet of whole-plant corn silage, Groups B, C, and D were fed with feeding rape at inclusion levels of 9.86% (low level), 12.45% (medium level), and 15.89% (high level), respectively. The results showed that feeding rape had no effects (P > 0.05) on meat quality indicators such as initial muscle moisture, crude ash, crude protein, and carcass yield. The medium and high levels increased the daily weight gain and decreased the feed-to-gain ratio (P < 0.05). The high level decreased carcass fat content value and intramuscular fat (IMF) (P < 0.05). Transcriptome analysis suggested that the decrease in intramuscular fat may be related to the regulation of genes such as LPL, FABP4, PLIN1, EHHADH, SCD, and ACOX2. In summary, feeding rape can be used as a source of roughage. However, when aiming to increase IMF deposition, the additional level of rape in the feed should be carefully considered.